Should vitamin K be supplemented instead of antagonised in patients with idiopathic pulmonary fibrosis?. (4th March 2018) - De Brouwer, Bart; Piscaer, Ianthe; Von Der Thusen, Jan H.; Grutters, Jan C; Schutgens, Roger EG.; Wouters, Emiel FM.; Janssen, Rob
ABSTRACT: Introduction : There is an ongoing need for additional interventions in idiopathic pulmonary fibrosis (IPF) as antifibrotic drugs currently available only inhibit and do not stall disease progression. Vitamin K is a co-factor for the activation of coagulation factors. However, it is also required to activate proteins with functions outside of the coagulation cascade, such as matrix Gla protein (MGP), a defender against soft tissue calcification. Vitamin K antagonists are anticoagulants that are, for unknown reasons, associated with increased mortality in IPF. Areas covered : We advance the hypothesis that modulation of vitamin K-dependent MGP activation in IPF patients by either vitamin K antagonism or administration may result in acceleration and deceleration of fibrosis progression, respectively. Furthermore, shortfall in vitamin K could be suspected in IPF based on the high prevalence of certain co-morbidities, such as vascular calcification and lung cancer. Expert commentary : We hypothesize that vitamin K status is reduced in IPF patients. This, in combination with studies suggesting that vitamin K may play a role in lung fibrosis pathogenesis, would provide a rationale for conducting a clinical trial assessing the potential mitigating effects of vitamin K administration on progression of lung fibrosis, prevention of co-morbidities and mortality in IPF.